Syekh Muhammad Jawad Maghniyah's Interpretation Methodology in Tafsir Al-Kasyif on Qs Al-Mudatsir - Ayu Sulastri; Noor Muhammad Rizki Kamil; Widyanto Naufal Mahdy (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Tafsir al-Kasyif is an Iqna'i-style tafsir with a literary approach in its explanation. The purpose of writing this tafsir is so that readers are expected to accept that religion Actually encompasses all its main points, branches and teachings that aim for the good, glory and success of all people. The purpose of this study is to determine the writing method of tafsir al-Kasyif in Q.S al-Mudatsir. This study uses a qualitative method through a literature review. The results of this study indicate that the tafsir al-Kasyif written by Sheikh Muhammad Jawad Maghniyah has a special method in writing his tafsir, including writing the name of the surah and its position, grouping verses, explaining linguistic analysis, explaining the meaning of each verse, including the munasabah of verses, and including the opinions of scholars. Based on this special method, it can make it easier for readers to understand the purpose and content of tafsir Al-Kasyif.